A light-controlled one-tube detection platform combining CRISPR-Cas12a and RPA: an innovative approach for rapid diagnosis of Acinetobacter baumannii - Zhou, Zihan; Pan, Lele; Luo, Shihua; Ma, Jiangmei; Ren, Baoyan; Liang, Lina; Li, Xuebin; Wei, Guijiang (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAcinetobacter baumannii (A. baumannii) is a significant pathogen associated with nosocomial infections, predominantly affecting immunocompromised patients, and is linked to high mortality rates. To control infection rates, there is an urgent need for a diagnostic method that is cost-effective, rapid, and user-friendly, meeting the current demand for timely diagnosis.MethodsWe have developed a one-tube detection method for UV light unlocking based on RPA-CRISPR/Cas12a technology. This method utilizes the photodegradable chemical group NPOM-dt to chemically modify the crRNA base, preventing it from complementary pairing with the base of the target molecule, thereby temporarily silencing the CRISPR system. After RPA preamplification, the caged modification group on the crRNA was removed with brief irradiation with ultraviolet light to restore the activity of the CRISPR/Cas12a. system.ResultsOur results demonstrated that the detection system achieved a limit of detection as low as 10 copies/μL for target fragments, with no cross-reactivity observed with genomic DNA from six clinically common pathogenic bacteria, showcasing excellent sensitivity and specificity. Additionally, clinical validation was performed using 38 sputum samples. The system successfully identified A. baumannii in sputum specimens, with results consistent with those obtained via conventional PCR.ConclusionWe have successfully developed a light-controlled one-tube RPA-CRISPR/Cas12a detection system. It simplifies the operation and at the same time greatly reduces the risk of laboratory contamination caused by repeated tube opening, providing a new idea for the development of point-of-care testing (POCT).